Rotor, its manufacturing method and electric motor
The rotor design with a soft magnetic body and a specifically formulated bonded magnet effectively addresses the challenge of rotor deformation at high speeds, ensuring structural integrity and improved motor performance.
Patent Information
- Application Number
- JP2023550875
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-09-29
Smart Images

Figure 0007654813000002 
Figure 0007654813000003 
Figure 0007654813000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a rotor for an electric motor, etc. [Background technology]
[0002] There are various types of electric motors (including generators, simply called "motors"). Recently, with the development of inverter control and the widespread use of rare earth magnets with high magnetic properties, synchronous machines, which offer the promise of low power consumption, high efficiency, high torque, and high output, have been attracting attention.
[0003] A synchronous machine is a permanent magnet field motor with a permanent magnet (field source) in the rotor and an armature (windings) in the stator. A synchronous machine is an AC motor in which alternating current (AC) is supplied to the windings and the rotor is driven in response to the rotating magnetic field generated on the stator side. Synchronous machines include internally-encapsulated magnet motors (also called "IPM motors") in which permanent magnets are disposed (embedded) within the rotor, and surface-magnet motors (also called "SPM motors") in which permanent magnets are disposed on the outer circumferential surface side of the rotor.
[0004] The permanent magnets arranged in the rotor are classified into sintered magnets made by sintering magnetic powder, and bonded magnets made by binding magnetic powder with a binder resin. Bonded magnets have a greater degree of freedom in shape than sintered magnets and are also more productive, so they are increasingly being used as the field source for the rotor.
[0005] Bonded magnets are further divided into injection bonded magnets, which are made by injection molding a molten mixture of magnet powder and thermoplastic resin in a cavity (such as a slot in a rotor core), and compression bonded magnets, which are made by compression molding a mixture or kneaded product of magnet powder and thermosetting resin in a cavity. Compression bonded magnets generally have better magnetic properties and heat resistance than injection bonded magnets. The following patent documents contain descriptions related to such conventional compression bonded magnets. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 3731597 [Patent Document 2] JP 2006-49554 A Summary of the Invention [Problem to be solved by the invention]
[0007] The above patent documents only focus on the magnetic properties of bonded magnets, and make no mention of the effects that bonded magnets have on the strength or deformation of a rotor that may rotate at high speeds.
[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide a rotor etc. that uses a bonded magnet as a field source and is resistant to deformation even in the high speed rotation range. [Means for solving the problem]
[0009] The inventors conducted extensive research to solve this problem and discovered that a specific type of bonded magnet can be strongly bonded to the soft magnetic material (the rotor body) and suppress deformation of the rotor in the high speed rotation range. By expanding on this result, the inventors have completed the present invention, which will be described below.
[0010] Rotor (1) The present invention relates to a rotor having a main body made of a soft magnetic material and a permanent magnet provided inside or on the outer periphery of the main body, the permanent magnet being a bonded magnet made of magnet powder and a binder resin that binds the magnet powder, the bonded magnet containing 87 to 96 mass% of the magnet powder relative to the entire bonded magnet, the magnet powder containing coarse powder having an average particle size of 40 to 200 μm and fine powder having an average particle size of 1 to 10 μm, the mass ratio of the coarse powder to the total of the coarse powder and the fine powder being 60 to 90 mass%, the binder resin containing a thermosetting resin, and the bonded magnet being bonded to the main body.
[0011] (2) The rotor of the present invention is less likely to deform even in the high-speed rotation range, and can contribute to the high speed and high output of electric motors. The reason for this is believed to be that the bonded magnet of the present invention is firmly bonded to the main body (rotor core) made of soft magnetic material. For example, in the case of an IPM motor, the bonded magnet of the present invention is strongly bonded to the inner wall of the slot (magnet hole) provided in the main body. This allows the bonded magnet to maintain its integrity with the main body even under high-speed rotation. As a result, even when a large centrifugal force is applied, the stress distribution of the rotor is generally low, and stress concentration in a part of the main body (for example, near the bridge part on the outer periphery of the slot) is also avoided. In this way, deformation and damage of the rotor (especially the main body) are suppressed even under high-speed rotation, which in turn enables the motor to rotate at high speed and have high output.
[0012] 《Electric motor》 The present invention can also be understood as an electric motor having the above-mentioned rotor. The electric motor may have a stator corresponding to the rotor. Note that the electric motor (motor) referred to in this specification includes a generator.
[0013] "others" Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit value or upper limit value to create a new range such as "a to b". Furthermore, unless otherwise specified, "x to y μm" in this specification means x μm to y μm. The same applies to other unit systems (MPa, kA / m, etc.). [Brief description of the drawings]
[0014] [Figure 1A] 1 is a photograph showing a test piece for measuring bonding strength and a mold used for producing the test piece. [Figure 1B] Photographs showing the tensile test device and the broken test piece are shown. [Diagram 2] 1 is a graph showing the relationship between the bonding strength of the test piece and the amount of magnetic powder contained in the bonded magnet of the test piece. [Diagram 3]This is a magnified (20,000x) observation image of the vicinity of the bonded interface of the test piece (sample 4). [Figure 4] FIG. 1 is a model diagram used for numerically analyzing the stress distribution generated in a rotor for an IPM motor. [Figure 5A] Based on the results of the numerical analysis, the following graph shows the relationship between the maximum value of the maximum principal stress generated in the rotor and its rotation speed, and a contour diagram showing the distribution of the maximum principal stress generated in the rotor (at 34,000 rpm). [Figure 5B] Based on the results of the numerical analysis, the following graph shows the relationship between the maximum value of the maximum principal stress generated in the bonded magnet in the rotor and its rotation speed, and a contour diagram showing the distribution of the maximum principal stress generated in the bonded magnet (at 34,000 rpm). [Figure 6] 1 is a graph showing the relationship between the rotation speed of a rotor (actual object) and the amount of deformation of its outer diameter when a spin test was performed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] One or more components selected from the items described in this specification may be added to the above-mentioned configuration of the present invention. The components may be related to the manufacturing method or the product. Which embodiment is best depends on the target, required performance, etc.
[0016] 《Main body》 The main body is made of a soft magnetic material because it constitutes part of the magnetic circuit. Soft magnetic materials are, for example, pure metals or alloys made of iron group elements (Fe, Co, Ni). Representative examples of soft magnetic materials include pure iron and iron alloys (Fe-Si alloys, etc.).
[0017] In order to reduce eddy current loss (also simply called "iron loss") that occurs in the main body while the motor is in operation, it is preferable that the main body has a large resistivity (volume resistivity). For example, the main body may be a laminate of electromagnetic steel sheets made of steel sheets (e.g., silicon steel sheets) with an insulating coating on at least one surface, or a green compact made of soft magnetic particles with an insulating coating on the surface. The main body, which is subject to a large centrifugal force due to high-speed rotation, should be made of a laminate of electromagnetic steel sheets. The lamination direction should be a direction in which eddy currents are blocked by the insulating layer (usually the direction of the rotation axis). The electromagnetic steel sheets may be bonded (laminated) to each other by any of caulking, adhesive bonding, fastening, etc.
[0018] The thickness of the laminated magnetic steel sheets is, for example, 0.1 to 1 mm, 0.2 to 0.7 mm, or even 0.3 to 0.5 mm. If a magnetic steel sheet that is too thin is used, the amount of relatively non-magnetic insulating layers increases, which may increase magnetic resistance and costs. Conversely, if a magnetic steel sheet that is too thick is used, eddy current loss increases, which may reduce the efficiency of the motor. Note that "steel" as used in this specification includes silicon steel, carbon steel, pure iron, and the like, regardless of alloy elements (including impurity elements) other than Fe. In the case of a silicon steel sheet, Si is contained in an amount of, for example, 0.5 to 7 mass % or even 2 to 4 mass % relative to the entire steel.
[0019] Bonded Magnets (1) A bonded magnet is composed of a large number of magnet particles and resin (including rubber, elastomer, various additives, etc.), which is the portion other than the magnet particles. Surface treatment agents for the magnet particles are considered to be included in the "magnet particles". For ease of explanation, in this specification, not only the aggregate of magnet particles that is the raw material for the bonded magnet, but also the "large number of magnet particles" that make up the bonded magnet itself are referred to as "magnet powder".
[0020] In order to ensure the strength of a rotor capable of rotating at high speeds and to suppress deformation, it is preferable that the bonded magnet itself has sufficient strength relative to the bonding strength between the bonded magnet and the main body. For this reason, it is preferable that the bonded magnet is dense and has few voids that can become the starting points of cracks, etc.
[0021] For example, the relative density of a bonded magnet should be 90% or more, 95% or more, or even 98% or more. The upper limit of the relative density is 99.5% or even 100%. The relative density (ρ / ρ0) is calculated as the ratio (percentage) of the actual density (ρ) to the theoretical density (ρ0). The theoretical density (ρ0) is calculated from the true density of the magnetic powder and binder resin that make up the bonded magnet and their mixed amounts. The actual density (ρ) is calculated from the mass and volume obtained by measuring the bonded magnet that has been molded (and cured). The volume may be calculated using the Archimedes method, but it is sufficient to calculate it from the shape (dimensions) of the molded body.
[0022] (2) Magnetic powder It is advisable for the magnet powder (magnet particles) to contain coarse powder (coarse particles) and fine powder (fine particles) with different average particle sizes, which will result in a dense bonded magnet with improved strength and magnetic properties.
[0023] The average particle size of the coarse powder is, for example, 40 to 200 μm, or 80 to 160 μm. The average particle size of the fine powder is, for example, 1 to 10 μm, or 2 to 6 μm. The average particle size referred to in this specification is determined by measuring the powder (including magnet particle groups recovered from bonded magnets) by the Fraunhofer method using a laser diffraction type particle size distribution measuring device (HELOS, manufactured by Nippon Laser Co., Ltd.).
[0024] The mass ratio of the coarse powder to the total of the coarse powder and the fine powder (or the entire magnet powder) is, for example, 60 to 90 mass%, or 75 to 85 mass%, in other words, the mass ratio of the fine powder to the total is, for example, 10 to 40 mass%, or 15 to 25 mass%.
[0025] The mass proportion of the entire magnet powder relative to the entire bonded magnet (total of magnet powder and binder resin) is, for example, 87 to 96 mass %, 88 to 95.5 mass %, 90 to 95 mass %, 91 to 94.5 mass %, or even 92 to 94 mass %.
[0026] Whether the amount of magnetic powder (simply called "magnet amount") in the overall bonded magnet is too little or too much, the bond strength between the bonded magnet and the main body can decrease. If the amount of magnet is too little (if the amount of resin is too much), a thick resin layer is formed near the bonded interface, and it is thought that this resin layer will be prone to cohesive failure. Conversely, if the amount of magnet is too much (if the amount of resin is too little), there will be more contact between the magnetic particles and the main body near the bonded interface, and it is thought that the interface will be prone to failure.
[0027] Various magnet powders can be used for the coarse powder and the fine powder, and each powder may have the same or different composition and manufacturing method. At least one of the coarse powder and the fine powder may be a mixed powder of magnet powders with different compositions, manufacturing methods, characteristics, etc. Each powder may be an isotropic magnet powder, an anisotropic magnet powder, or a mixture thereof. Using an anisotropic magnet powder improves the magnetic properties of the bonded magnet, thereby increasing the output of the electric motor.
[0028] An example of the coarse powder is NdFeB magnet powder, whose base components (essential or main components) are Nd, Fe, and B. An example of the fine powder is SmFeN magnet powder, whose base components are Sm, Fe, and N, or SmCo magnet powder, whose base components are Sm and Co. As the fine powder (part), NdFeB magnet powder with particle size adjustment may be used. A part of each powder may contain magnet powder other than rare earth magnet powder (such as ferrite magnet powder).
[0029] The total amount of the elements that are the base components in this specification is usually 80 atomic % or more, 90 atomic % or more, or even 95 atomic % or more of the entire target object (magnet particles). The rare earth magnet powder may contain elements (heavy rare earth elements such as Dy and Tb, Cu, Al, Co, Nb, etc.) that increase the coercive force and heat resistance, etc.
[0030] A typical example of coarse powder is hydrogen-treated rare earth (anisotropic) magnet powder. Hydrogenation mainly involves a disproportionation reaction caused by hydrogen absorption (also simply called the "HD reaction") and a recombination reaction caused by desorption (also simply called the "DR reaction"). The HD reaction and the DR reaction are collectively referred to simply as the "HDDR reaction." Furthermore, the hydrogen treatment that produces the HDDR reaction is simply referred to as "HDDR (treatment)."
[0031] Unless otherwise specified, the HDDR referred to in this specification includes an improved d-HDDR (dynamic-Hydrogenation-Disproportionation-Desorption-Recombination) method. d-HDDR is described in detail in, for example, International Publication WO2004 / 064085.
[0032] Incidentally, the magnet particles may be surface-treated with a surfactant suitable for the binder resin. This can improve the binding between the magnet particles and the resin, and the positional variability of the magnet particles in the softened or molten resin. Examples of the surfactant include titanate-based coupling agents and silane-based coupling agents. The thickness of the surfactant layer may be about 0.1 to 2 μm.
[0033] (3) Binder resin The binder resin contains a thermosetting resin, which allows the bonded magnet to be firmly bonded to the main body. In this specification, unless otherwise specified, the area (portion) other than the magnet powder (particles) is called the binder resin (or simply "resin"). "Resin" includes, for example, the base agent, hardener, hardening accelerator, release agent, etc.
[0034] Thermosetting resins include epoxy resins, phenolic resins, melamine resins, urea resins, and unsaturated polyester resins. A typical epoxy resin is usually a mixture of a prepolymer and a curing agent, and is cured by forming a crosslinked network with epoxy groups. Examples of epoxy resin prepolymers include novolac type, bisphenol A type, bisphenol F type, biphenyl type, naphthalene type, aliphatic type, and glycidylamine type. Examples of epoxy resin curing agents include amine type, phenol type, and acid anhydride type. The thermosetting resin may be a one-component type.
[0035] (4) The bonded magnet should have characteristics (magnetic properties, heat resistance, demagnetization resistance, etc.) that are suitable for the specifications of the rotor (electric motor). For example, the residual magnetic flux density (Br), which is an index of magnetic properties, may be 0.70T (7.0kG) or more, 0.72T (7.2kG) or more, 0.74T (7.4kG) or more, 0.76T (7.6kG) or more, 0.78T (7.8kG) or more, or 0.80T (8.0kG) or more. Also, Hk may be, for example, 535kA / m or more, 540kA / m or more, or even 545kA / m or more. Hk is determined as the magnitude of the reverse magnetic field when the residual magnetic flux density Br of the bonded magnet decreases by 10%. Hk is an index of reverse magnetic field resistance or squareness, which is important for bonded magnets used in electric motors.
[0036] Rotor The rotor is made by bonding a bonded magnet to a main body. In the vicinity of the bonding interface between the bonded magnet and the main body, it is preferable to have a resin layer made of, for example, a binder resin. The average thickness of the resin layer is, for example, 0.1 to 5 μm, 0.2 to 4 μm, 0.3 to 3 μm, 0.4 to 2 μm, or even 0.5 to 1.5 μm.
[0037] As mentioned above, if the resin layer is too thick, it is more likely to undergo cohesive failure. If the resin layer is too thin, the magnet particles come into direct contact with the main body, which makes it more likely to undergo interface failure. It is also preferable that the resin layer be largely continuous with few discontinuities.
[0038] The average thickness of the resin layer is determined by analyzing a microscope image of the bonded interface. For example, it is determined as the arithmetic mean value of the distance between the main body surface and the magnet particle surface measured at 0.1 μm intervals along the main body surface within a specified field of view (6 μm × 4.5 μm) (see Figure 3). The average thickness of the resin layer may be determined using image analysis software (ImageJ, etc.).
[0039] The bond strength between the bonded magnet and the main body should be, for example, greater than the maximum principal stress (and even its maximum value) acting on the bonded magnet (for example, on the inner peripheral surface side (rotating shaft side)). Although it depends on the rotor specifications and the motor specifications (rotation speed, etc.), if one dares to say, the lower limit of the bond strength is, for example, 10 MPa, 15 MPa, 20 MPa, or even 25 MPa. The higher the upper limit of the bond strength, the better, for example, 55 MPa, 45 MPa, or even 35 MPa. It should be noted that the bonded magnet should have a tensile strength sufficiently greater than the above-mentioned maximum principal stress and bond strength.
[0040] The rotor may be an inner rotor with a stator on its outer periphery, or an outer rotor with a stator on its inner periphery. The number of magnetic poles of the rotor, its support structure, etc. are appropriately selected according to the specifications of the electric motor.
[0041] 《Electric motor》 The electric motor may be a DC motor or an AC motor. The AC motor may be, for example, an IPM motor or an SPM motor. In particular, an IPM motor having an internal magnet type rotor in which a bonded magnet is bonded to a main body made of a soft magnetic material inside the main body is suitable for high-speed operation. The maximum rotation speed of the rotor may be, for example, 20,000 rpm or more, 23,000 rpm or more, 27,000 rpm or more, or even 30,000 rpm or more. The electric motor may be used, for example, as a drive motor for vehicles, air conditioners, home appliances, etc. The bonded magnet may be bonded to the main body at the time of molding (for example, during compression integral molding).
[0042] <Rotor manufacturing method> (1) The rotor is obtained, for example, by molding a bonded magnet inside or on the outer periphery of a main body made of a soft magnetic material. The bonded magnet is bonded to the main body during molding or during a heat curing process after molding. The inside of the main body is, for example, the slots (magnet holes) of a rotor core for an IPM motor. The form of the slots (shape, size, arrangement, number of slots per magnetic pole, etc.) is not important. The outer periphery of the main body is, for example, the outer periphery surface of a rotor core for an SPM motor or the area nearby. The bonded magnet of an SPM motor is, for example, tile-shaped or annular.
[0043] (2) Bonded magnet raw materials The bonded magnet raw material may be, for example, a mixed powder of magnet powder and binder resin, a mixture of molten or softened binder resin and magnet powder, a kneaded product of the mixture, a solidified mixture or a granular compound made of the kneaded product, or a preformed compound formed into a desired shape.
[0044] The mixing and kneading of the magnet powder and the binder resin is carried out by heating, for example, to about 40 to 120° C. or about 80 to 100° C. depending on the type and composition of the binder resin. When using magnet powder obtained by hydrogen treatment, the mixing and kneading may be carried out under heating without applying pressure.
[0045] The preform is made of a block of mixed powder or compound in a specific form (shape, size). The preform may be similar to a bonded magnet or may be dissimilar to a bonded magnet (such as a finely divided body that can be inserted into a cavity). The preform containing the magnet powder obtained by hydrogen treatment is preferably molded at a low pressure (for example, 2 MPa or less, or even 0.5 MPa or less).
[0046] (3) Molding process A bonded magnet is obtained, for example, by heating and compressing raw material for a bonded magnet in a cavity provided inside or on the outer periphery of a main body.
[0047] The heating temperature is, for example, 120 to 200°C, or further 130 to 170°C. If the heating temperature is too low, the binder resin will not soften or melt sufficiently. If the heating temperature is too high, the thermosetting resin will harden prematurely. In either case, the bonding strength between the bond magnet and the main body may decrease.
[0048] The compression force (molding pressure) is, for example, 8 to 70 MPa, 10 to 65 MPa, 15 to 60 MPa, 20 to 50 MPa, or even 30 to 40 MPa. If the compression force is too small, the relative density and strength of the bonded magnet may decrease. If the compression force is too large, deformation of the main body may occur. Note that bonded magnets with a relatively large amount of resin are dense and can exhibit high strength and magnetic properties even when molded at low pressure.
[0049] When anisotropic magnet powder is contained in the bonded magnet raw material, it may be molded in an aligning magnetic field. The aligning magnetic field is usually applied in a direction (alignment direction) that intersects with the compression direction of the bonded magnet raw material. The magnitude of the aligning magnetic field (magnetic flux density on the inner peripheral surface of the cavity) is, for example, 0.5 to 3 T, or even 1 to 2 T. In addition to electromagnets, rare earth permanent magnets may be used as the magnetomotive source of the aligning magnetic field.
[0050] A thermosetting treatment (cure treatment) of the thermosetting resin may be carried out after molding. This can improve the bonding strength between the bonded magnet and the main body, and the strength and heat resistance of the bonded magnet itself. The cure treatment is carried out, for example, by heating the bonded magnet to 130 to 250°C, or even 150 to 230°C. The cure treatment is carried out, for example, by batch processing in which the integrated main body and bonded magnet are heated separately. EXAMPLES
[0051] [First Example] A number of test pieces were produced by bonding a bonded magnet to a core (main body), and the bonding strength of these test pieces was measured. The present invention will be described in detail below based on these specific examples.
[0052] <Sample Preparation> (1) Bonded magnet raw materials The magnet powders used were a commercially available NdFeB-based anisotropic magnet powder (Magfine, manufactured by Aichi Steel Corporation; Br / Br: 1.28 T, iHc: 1313 kA / m, average particle size: 125 μm), which is a coarse powder produced by hydrogen treatment (d-HDDR), and a commercially available SmFeN-based anisotropic magnet powder (SmFeN alloy fine powder, manufactured by Sumitomo Metal Mining Co., Ltd.; C / Br: 1.35 T, iHc: 875 kA / m, average particle size: 3 μm), which is a fine powder.
[0053] As the binder resin, epoxy resin (hereinafter referred to as "EP"), which is a thermosetting resin, and polyphenylene sulfide resin (hereinafter referred to as "PPS"), which is a thermoplastic resin, were prepared.
[0054] EP is made by kneading the following raw materials: Main agent (NC-3000L manufactured by Nippon Kayaku Co., Ltd.): 100 parts by weight, Hardener (GPH-65 manufactured by Nippon Kayaku Co., Ltd.): 74 parts by mass, Curing accelerator (TPP-S manufactured by Hokko Chemical Co., Ltd.): 3 parts by weight Release agent (Carnauba wax manufactured by Cerarica NODA Co., Ltd.): 2.6 parts by weight
[0055] The softening point of the EP was 60° C. An EP not containing the above-mentioned release agent was also prepared (adhesive sample D2 / see Table 1).
[0056] The magnet powder and binder resin were mixed in the ratios shown in Table 1 to prepare the bonded magnet raw materials (samples 1 to 7). The magnet powder is composed of coarse powder and fine powder, and the mass ratio (volume ratio is roughly the same) of the coarse powder to the total amount is also shown in Table 1.
[0057] The magnet powder and the binder resin were mixed for 5 minutes in a non-pressurized state with the kneader rotating at a low speed (10 rpm). At this time, the kneader's temperature was kept at 90° C. In this way, a compound in which the magnet powder and the binder resin were melted and mixed was obtained (melt mixing process).
[0058] (2) Core A core (dummy) for the test piece simulating a rotor core was prepared. The core was a rectangular parallelepiped (12.7 mm x 12.7 mm x 17.5 mm) cut from a laminate of electromagnetic steel sheets (non-oriented electromagnetic steel strip 20JNEH1200 manufactured by JFE Steel Corporation, thickness 0.2 mm). The laminate was made by bonding electromagnetic steel sheets together with an adhesive. The laminate was cut by wire cutting so that the laminated surface of the electromagnetic steel sheets appeared on the end face of the core (□12.7 mm). The wire-cut end face of the core was smooth (surface roughness Ra: about 1.6 μm) with no visible irregularities.
[0059] (3) Molding A mold was prepared with a cavity (12.7 mm x 12.7 mm x 79 mm) in the center as shown in Figure 1A. A core was placed on each end of the cavity. The compound was filled between the cores (center of the cavity / 12.7 mm x 12.7 mm x 3 mm) and heated to about 150°C for compression molding (molding process). The compression force was about 20 to 50 MPa.
[0060] In this way, a rectangular parallelepiped test piece (12.7 mm x 12.7 mm x 79 mm) was obtained in which both cores and the bonded magnet were compression molded together (insert molding) (see Figure 1A).
[0061] (4) Cure treatment The test pieces (samples 1 to 7) were heated in air at 150° C. for 30 minutes to thermally cure the EP, and then subjected to a tensile test.
[0062] <<Preparation of Comparative Samples>> (1) As shown in Table 1, a test piece (sample A1) was also prepared by injecting a molten mixture of bonded magnet raw material (S5P-13MF manufactured by Sumitomo Metal Mining Co., Ltd.) with PPS as the binder resin into the mold, and molding the bonded magnet and core together. The injection pressure was 100 MPa.
[0063] (2) A test piece (sample B1) was also prepared by compressing and molding only EP, which did not contain magnetic powder, and a core together. The compressive force was set to about several MPa.
[0064] (3) A test piece (specimen C1) was also prepared by bonding a separately prepared bonded magnet (12.7mm x 12.7mm x 3mm) to the core with adhesive, instead of molding it as a single piece. A compression molded bonded magnet (see sample 4) was used for sample C1. Adhesive A (LOCTITE4061 manufactured by Henkel) was used for sample C1.
[0065] (4) Test pieces (samples D1-D2 / 12.7mm x 12.7mm x 76mm) were also prepared in which the cores were directly bonded together with an adhesive without the use of a magnet. EP was used as the adhesive for samples D1 and D2. However, for sample D2, EP that did not contain the above-mentioned release agent was used. All test pieces were subjected to a curing treatment (see samples 1-7), and all EPs were thermally cured.
[0066] For all samples, the thickness of the magnet attached to the core (the length in the extension direction of the test piece) was 3 mm, and the thickness of the adhesive layer was approximately 5 μm. The thickness of the adhesive layer was confirmed with a micrometer.
[0067] Measurement and Observation (1) Tensile test Both core parts of the test piece were gripped with an autograph (Shimadzu Corporation AGS-J 5kN) shown in Figure 1B, and a uniaxial tensile load was applied to the test piece. The measured load at which the test piece broke was divided by its cross-sectional area (12.7mm x 12.7mm) to determine the bonding strength. The bonding strength of each test piece is summarized in Table 1. For reference, an example of a test piece that broke after the tensile test (sample 4) is also shown in Figure 1B. Furthermore, the relationship between the bonding strength and the amount of magnet powder for samples 1 to 7 is shown in Figure 2.
[0068] (2) Observation For the test piece of sample 4, which has a high bonding strength, the vicinity of the bonding interface between the bonded magnet and the core was observed with a scanning electron microscope (SEM). The observed image is shown in Figure 3. The black parts in Figure 3 are the binder resin (EP).
[0069] An orthogonal mesh with 0.1 μm intervals was applied to the observed image (field of view: 6 μm × 4.5 μm). The horizontal axis of the mesh was set along the core joint interface. Using this mesh, the average thickness of the resin layer near the core surface (near the joint interface) was found. Specifically, the length in the vertical axis direction from the core surface to the magnet particles was measured at 0.1 μm intervals, and the arithmetic average value was found. As an example, the average thickness of the resin layer in sample 4 was 0.62 μm.
[0070] "evaluation" (1)Join strength As is clear from Table 1 and FIG. 2, it was found that the bonding strength between the bonded magnet and the core increases significantly when the amount of magnet powder (mass % / amount of resin=100-amount of magnet powder) is within a specified range.
[0071] Incidentally, as can be seen by comparing sample 4 and sample C1, which have the same bonded magnet composition, the bonding strength achieved by compression molding is far greater than that achieved by bonding with an adhesive. As is clear from samples B1, D1, and D2, it was also found that it is difficult to firmly bond the cores together using only binder resin.
[0072] It should be noted that "bonding strength" refers to the tensile strength (breaking load / nominal cross-sectional area) between the cores that sandwich the bonded magnet, regardless of the failure mode between the cores (interfacial failure or cohesive failure).
[0073] Furthermore, when the above-mentioned tensile test was simulated using a test piece with a total length of 79 mm (core distance: 3 mm), it became clear that the test piece had a stress concentration area where a stress of about 1.5 times the joint strength shown in Table 1 occurred. In the tensile test, it is believed that the test piece broke from that stress concentration area. Taking this into consideration, it is believed that the net joint strength between the bonded magnet and the main body (samples 1 to 7) is even greater than the joint strength shown in Table 1.
[0074] (2) Resin layer The reason why samples 3 to 5 showed a peak of high bonding strength is thought to be that a resin layer of appropriate thickness was formed near the bonding interface, as shown in Figure 3. On the other hand, when there was a lot of binder resin, as in samples 1 and 2, a thick resin layer was formed, and it is thought that cohesive failure occurred in that resin layer. Conversely, when there was little binder resin, as in samples 6 and 7, there were many discontinuities in the resin layer where the magnet particles directly contacted the core surface, and it is thought that interface failure occurred.
[0075] Incidentally, sample D1, which has a very thin resin thickness of about 5 μm, had a much stronger bond strength than sample B1, which has a thick resin thickness of 3 mm between the cores. This is thought to be related to one of the factors that causes high bond strength to be exhibited when a resin layer with an average thickness of about 0.1 to 5 μm is located near the bonded interface with the core (main body).
[0076] 《Consideration》 In conventional rotors for IPM motors that use bonded magnets as the field source, the bonded magnet and rotor core are injection molded as a single unit. In rotors like this, the bond strength between the bonded magnet and rotor core is low (see sample A1), so the maximum rotation speed is limited. On the other hand, in rotors where the bonded magnet and rotor core are compression molded as a single unit, the bond strength between the bonded magnet and rotor core is significantly greater (see samples 3 to 5), and a significant increase in the maximum rotation speed is expected.
[0077] "supplement" (1) Bonded magnets The bonded magnets of samples 1 to 7 had a tensile strength of about 50 to 70 MPa, which was sufficiently greater than the joint strength, and the relative density of the bonded magnets was about 98%, which was sufficiently dense.
[0078] (2) Core A test specimen was also produced in which the core made of the laminated magnetic steel sheets was replaced with a core made of a solid cemented carbide alloy (non-magnetic cemented carbide NF-30 (NA20) manufactured by Sanalloy Industry Co., Ltd.) The joining surface of the core (□12.7 mm) was mirror-finished.
[0079] The test pieces were used to carry out the tensile tests described above in the same manner. As a result, it was found that, for example, a test piece manufactured by compression molding in the same manner as sample 4 showed a bonding strength as high as that of sample 4. From this, it is considered that the properties of the core's bonding surface (fine irregularities, surface roughness, etc. / see Figure 3) have little or no effect on the bonding strength.
[0080] (3) Magnetic properties The magnetic properties of the bonded magnets pertaining to Samples 1 to 7 were measured at room temperature using a DC BH tracer (TRF-5BH-25Auto, manufactured by Toei Kogyo Co., Ltd.). The bonded magnets used for the measurements were heat-compressed (150°C x 10 to 50 MPa) in an orienting magnetic field (955 kA / m) and then magnetized (applied magnetic field: 6 T). All of the bonded magnets (especially Samples 3 to 5) exhibited sufficient magnetic properties. As an example, the bonded magnet corresponding to Sample 4 had Br: 0.80 T and Hk: 543 kA / m.
[0081] [Second Example] The stress distribution caused by centrifugal force was numerically analyzed (simulated) for a rotor for an IPM motor with a bonded magnet embedded in its core.The present invention will be described in detail below based on this specific example.
[0082] Analytical model The rotor model (planar 1 / 6 periodic symmetric model) used in the numerical analysis is shown in Figure 4. The rotor core is approximately cylindrical (outer diameter: φ59.8mm x hole diameter: φ13mm x height: 45mm). The slots provided in the rotor core are approximately arc-shaped (small radius: 11.29mm x large radius: 14.29mm x height: 45mm), and the slots are constant in the radial direction (width: 3mm). In this case, the apex P of the inner wall of the slot is 17.46mm from the center of rotation. The width of the bridge part (radial length of the rotor core on the outer peripheral end side of the slot): 0.5mm.
[0083] The rotor core is made of a laminate of electromagnetic steel sheets, and each sheet is fixed by caulking. The electromagnetic steel sheets are assumed to be 35H440 (thickness: 0.35 mm) manufactured by Nippon Steel Corporation, with a density of 7.7 g / cm 3The Young's modulus was 110 GPa, and the Poisson's ratio was 0.3. The number of laminated magnetic steel sheets was 128.
[0084] The bonded magnet to be embedded in the rotor core is assumed to be the bonded magnet related to sample 4 (Table 1), with a density of 5.5 g / cm 3 The Young's modulus was 4 GPa, and the Poisson's ratio was 0.3. The bonded magnet had the same shape as the slots of the rotor core.
[0085] Numerical Analysis Numerical analysis was performed on a rotor model in which the outer wall surface of the bonded magnet is bonded (integrated) with the inner wall surface of the slot (called "Model 1"), and a rotor model in which the outer wall surface of the bonded magnet is only in contact with the inner wall surface of the slot but is not bonded (called "Model C"). The constraint conditions were: fixed in the circumferential direction, friction coefficient: 0.1, load: centrifugal force, and rotation speeds: 8500 rpm, 17000 rpm, 25500 rpm, and 34000 rpm. The analysis software used was Abaqus2019 from Dassault Systèmes.
[0086] 《Analysis results》 Based on the analysis results, the relationship between the rotation speed and the maximum principal stress generated in the rotor is shown in Figure 5A. Similarly, the relationship between the rotation speed and the maximum principal stress generated in the bonded magnet is shown in Figure 5B. Each figure also shows an example (34,000 rpm) of the maximum principal stress distribution generated in the rotor or bonded magnet. Figures 5A and 5B are collectively referred to simply as "Figure 5."
[0087] "evaluation" (1) Rotor As is clear from FIG. 5A, it was found that the maximum stress occurs in the bridge portion of the rotor core in all models.
[0088] In the rotor (Model 1) where the bonded magnets are attached to the slots, the maximum principal stress was kept low even as the rotation speed increased. Since the yield stress of electromagnetic steel sheet (silicon steel sheet) is approximately 320 MPa (tensile strength is approximately 450 MPa), with the rotor of Model 1, no plastic deformation occurs even in the high rotation range.
[0089] On the other hand, in the rotor where the bonded magnets were simply inserted into the slots (Model C), the maximum principal stress increased sharply as the rotation speed increased. As a result, the rotor of Model C experienced significant plastic deformation at high rotation speeds. At 34,000 rpm, as can be seen in the stress distribution diagram, the rotor bulged toward the outer periphery to the extent that a gap appeared on the inner periphery of the bonded magnets.
[0090] (2) Bonded magnets As is clear from Figure 5B, in both models, the maximum principal stress generated in the bonded magnet increased as the rotation speed increased. Furthermore, the maximum principal stress in Model 1 was greater than that in Model C.
[0091] However, in the case of Model 1, even at 34,000 rpm, the maximum principal stress generated in the bonded magnet was about 19 MPa. At 25,500 rpm, the maximum principal stress was about 11 MPa.
[0092] 《Consideration》 This example shows that as long as the bonding strength between the bonded magnet and rotor core is greater than the maximum principal stress generated in the bonded magnet, the state of Model 1 is maintained and the maximum principal stress generated in the rotor is suppressed up to high speed rotation ranges. For example, with the high bonding strength shown in Example 1 (29.4 MPa for Sample 4), a rotor in which the rotor core and bonded magnet are integrated can achieve high speed rotation of 34,000 rpm or more (theoretically 42,000 rpm or more).
[0093] Incidentally, it can be seen from Fig. 5B that the maximum stress occurring in the bonded magnet itself occurs near vertex P. Therefore, the test piece of the first example was shaped such that the approximate center of the bonded magnet embedded in the rotor was cut out in the radial direction (the dashed line shape shown in Fig. 5B).
[0094] [Third Example] The rotor of the IPM motor that was actually manufactured was subjected to a spin test to evaluate the amount of deformation. Based on such a specific example, the present invention will be described in detail below.
[0095] <Making the rotor> Three types of rotors, C1, C2, were manufactured. The specifications of the rotor core were the same as those of the analysis model shown in the second example.
[0096] Rotor 1 is made by compressing and integrally molding bonded magnets into the slots. The composition and manufacturing conditions of the bonded magnets are the same as those of sample 4 (Table 1).
[0097] Rotor C1 is made by injection molding bonded magnets into the slots. The composition and manufacturing conditions of the bonded magnets are the same as those of sample A1 (Table 1).
[0098] Rotor C2 was made by inserting a separately injection molded bonded magnet into the slot. The composition and manufacturing conditions of the bonded magnet itself were almost the same as those of sample A1 (Table 1), but the bonded magnet was simply inserted into the slot without being adhered.
[0099] Spin Test (1) Test method The rotor was set in an air turbine spin tester (manufactured by Maruwa Denki Co., Ltd.) and rotated at high speed. The rotation speed was increased from 0 rpm at a rate of 2000 rpm / s. After reaching the predetermined measurement rotation speed, the rotor was held for 15 seconds, then removed and its outer diameter was measured. The measurement rotation speeds were 8000 rpm, 10000 rpm, 12000 rpm, 14000 rpm, 16000 rpm, 18000 rpm, 20000 rpm, 22000 rpm, 24000 rpm, 26000 rpm, and 28000 rpm.
[0100] (2)Outer diameter measurement The outer diameter of the rotor was measured at three points along the height direction (rotation axis direction), 5 mm, 22.5 mm, and 40 mm from the top end. For each measurement point, the outer diameter near the center of the magnetic pole (center of the bonded magnet) was measured in two intersecting directions. The arithmetic mean of the obtained outer diameter measurements (3 x 2 pieces) was taken as the outer diameter value for each measurement rotation speed. The difference between this outer diameter value and the initial outer diameter value (before testing) was taken as the amount of outer diameter deformation for each measurement rotation speed. The results are summarized in Figure 6.
[0101] "evaluation" As is clear from Figure 6, it was confirmed that the rotor 1 did not change in outer diameter and did not undergo plastic deformation even when rotated at high speeds of up to 28,000 rpm. This is believed to be because the bonded magnets are firmly attached to the rotor core (slots), dispersing the centrifugal force acting on the rotor and preventing stress concentration in bridges and other areas.
[0102] Incidentally, rotor C1, which has insufficient bonding strength between the bonded magnet and rotor core, experienced a rapid increase in plastic deformation above 20,000 rpm. Furthermore, rotor C2, in which the bonded magnet is not bonded to the rotor core, experienced a rapid increase in plastic deformation above 10,000 rpm.
[0103] From the above, it was confirmed that the rotor of the present invention is made of a bonded magnet firmly joined to a core (main body) and is capable of high speed rotation.
[0104] [Table 1]
Claims
1. A rotor comprising a main body made of a soft magnetic material and a permanent magnet provided inside or on an outer periphery of the main body, The permanent magnet is a bonded magnet made of magnet powder and a binder resin that binds the magnet powder, The bonded magnet contains 89.7 to 96 mass % of the magnetic powder relative to the entirety of the bonded magnet, the magnet powder comprises a coarse powder having an average particle size of 40 to 200 μm and a fine powder having an average particle size of 1 to 10 μm, the mass ratio of the coarse powder to the total of the coarse powder and the fine powder being 60 to 90 mass %, The binder resin includes a thermosetting resin, The bonded magnet is compression molded integrally with the main body to form a rotor.
2. 2. The rotor according to claim 1, wherein the bonded magnet has a resin layer having an average thickness of 0.1 to 5 μm near the joint interface with the main body.
3. 3. The rotor according to claim 1, wherein the thermosetting resin is an epoxy resin.
4. The coarse powder contains NdFeB-based magnet powder having Nd, Fe, and B as base components, 4. The rotor according to claim 1, wherein the fine powder contains SmFeN system magnet powder based on Sm, Fe and N and / or SmCo system magnet powder based on Sm and Co.
5. 5. The rotor according to claim 1, wherein the bonded magnet is formed by compression molding.
6. 6. The rotor according to claim 1, wherein the main body is made of a laminate of electromagnetic steel sheets.
7. An electric motor comprising the rotor according to any one of claims 1 to 6 and a stator corresponding to the rotor.
8. 8. The electric motor according to claim 7, wherein the rotor is an internal magnet type in which the bonded magnet is compressed and integrally molded inside the main body.
9. 9. The electric motor according to claim 8, wherein the maximum rotation speed of the rotor is 20,000 rpm or more.
10. The method includes a molding process in which a bonded magnet raw material consisting of magnet powder and binder resin is heated and compressed in a cavity provided inside or on the outer periphery of a main body, A manufacturing method for obtaining the rotor according to any one of claims 1 to 6.
11. The method for manufacturing a rotor according to claim 10, wherein the molding step is performed at a heating temperature of 120 to 200° C. and a compressive force of 8 to 70 MPa.
12. The method for manufacturing a rotor according to claim 10 or 11, further comprising the step of: carrying out a curing treatment after the molding step.
Citation Information
Patent Citations
Composite rare earth anisotropic bond magnet, compound for composite rare earth anisotropic bond magnet, and method for manufacturing them
JP2005116991A
Manufacturing method of polar anisotropy rare earth bond magnet and permanent magnet motor
JP2006049554A
Rotor for motor and manufacturing method therefor
JP2007074888A
Magnet-inclusion type synchronous machine and rotor thereof
JP2013143791A
Rare earth magnet powder, rare earth bond magnet, electric-motor element, and electric-motor
JP2018041882A